Observational Constraints on Varying Alpha in A（α）CDM Cosmology - 韦浩;薛冬泽 (理论物理通讯：英文版, 2017)
In this work, we consider the so-called A（α）CDM cosmology with A α-6 while the fine-structure ＂constant＂ a is varying. In this scenario, the accelerated expansion of the universe is driven by the cosmological ＂constant＂ A （equivalently the vacuum energy）, and the varying a is driven by a subdominant scalar field φ coupling with the electromagnetic field. The observationM constraints on the varying a and A α-6 models with various couplings By （φ） between the subdominant scalar field φ and the electromagnetic field are considered.